A RITUALIZAÇÃO DO ACONTECIMENTO MORTE NO JORNALISMO IMPRESSO DE PONTA GROSSA: UMA ANÁLISE DO DIÁRIO DOS CAMPOS, JORNAL DA MANHÃ E DIÁRIO DA MANHÃ - Verner, Afonso Ferreira (2017)
The research problematizes the ritualization of death, made by newspapers from Ponta Grossa. From the choice of four cases, spread over a period of 14 years (1998-2012), it presents an analysis of the coverage of newspaperss Diário dos Campos, Jornal da Manhã e Diário da Manhã. The violent death, in these periodicals, was ritualized between the extraordinary and the ordinary, result of a routine event or as a fact that destabilizes the series of daily and expected events, mobilizing responses from society and the journalistic narrative. The violent death composed, almost daily, the world portrait offered by the periodicals to the audience. Besides the analysis of the "Bruxo do Guaragi", 1998; Sônia Rocha, 1999; the death of the Agda model, 2011 and the mother responsible for the murders of the children in Palmeira, in the Campos Gerais region, in 2012, were discussed the daily death, found on the pages of the newspapers during the coverage period of the cases chosen. This analysis enabled a discussion about how newspapers makes the death event a vital substrate for the composition of the news and the world portrait presented to the audience. In addition, the study illustrates the use that journalistic narrative uses of imagery and textual aspects to make violent death an event presented among variations of "tragic", "macabre", "extraordinary", "shocking" and "shocking" up until death recorded in a protocolary way and without major significance in the news.